Toll-like receptor 3 mediates ischaemia/reperfusion injury after cardiac transplantation. (10th February 2020) - Gollmann-Tepeköylü, Can; Graber, Michael; Pölzl, Leo; Nägele, Felix; Moling, Rafael; Esser, Hannah; Summerer, Bianca; Mellitzer, Vanessa; Ebner, Susanne; Hirsch, Jakob; Schäfer, Georg; Hackl, Hubert; et al.
Abstract: OBJECTIVES: Ischaemia and subsequent reperfusion during heart transplantation inevitably result in donor organ injury. Toll-like receptor (TLR)-3 is a pattern recognition receptor activated by viral and endogenous RNA released by injured cells. We hypothesized that ischaemia/reperfusion injury (IRI) leads to RNA release with subsequent TLR3 activation in transplanted hearts. METHODS: Human endothelial cells were subjected to IRI and treated with TLR3 agonist polyinosinic–polycytidylic acid or a TLR3/double-stranded RNA complex inhibitor. TLR3 activation was analysed using reporter cells. Gene expression profiles were evaluated via next-generation sequencing. Neutrophil adhesion was assessed in vitro . Syngeneic heart transplantation of wild-type or Tlr3 −/− mice was performed following 9 h of cold ischaemia. Hearts were analysed for inflammatory gene expression, cardiac damage, apoptosis and infiltrating leucocytes. RESULTS: IRI resulted in RNA release with subsequent activation of TLR3. Treatment with a TLR3 inhibitor abrogated the inflammatory response upon IRI. In parallel, TLR3 stimulation caused activation of the inflammasome. Endothelial IRI resulted in TLR3-dependent adhesion of neutrophils. Tlr3 −/− animals showed reduced intragraft and splenic messenger ribonucleic acid (mRNA) expression of proinflammatory cytokines, resulting in decreased myocardial damage, apoptosis and infiltrating cells. Tlr3 deficiency protected from cardiac damage, apoptosis and leucocyte infiltration after cardiac transplantation. CONCLUSIONS: We uncover the release of RNA by injured cells with subsequent activation of TLR3 as a crucial pathomechanism of IRI. Our data indicate that TLR3 represents a novel target in the prevention of IRI in solid organ transplantation.